Non-Catalytic And Catalytic Fast Pyrolysis Of Lignocellulosic Biomass Into Bio-Oil Over Aluminosilicate-Based Catalysts - Tan, Yee Ling (2018)
Depletion of fossil resources and increasing motivation to develop renewable liquid fuels and chemicals have generated interest in the study of biomass conversion. This study aims to study the product yield and quality obtained from thermal and catalytic fast pyrolysis of durian shell, rattan and karanj shell in two-stage fixed-bed reactor over silica-alumina catalyst with different silica/alumina ratios, calcium- or iron-modified silica-alumina, and industrial waste-derived aluminosilicate catalysts. Effects of particle size (up to 5 mm) and pyrolysis temperature (250-650 'C) were investigated in thermal fast pyrolysis while the effects of catalytic temperature, catalyst/feedstock ratio, types of feedstock, and catalyst regeneration were determined in catalytic fast pyrolysis. The best temperature for liquid production for durian shell, rattan and karanj shell was 650 'C, 550 'C and 550 'C, respectively. Silica-alumina catalyst with microporous characteristic was synthesized using co-precipitation method. The bio-oil produced from durian shell over silica-alumina catalyst with silica/alumina ratio of 5.1 (SA-5.1) at 600 'C has deoxygenation degree of 93.61% with 75.45% aromatics content. The addition of calcium reduced coke deposition on SA-5.1 while iron promoted the yield of aromatics and hydrocarbons. Electric-arc-furnace-slag-derived catalyst (AS-EAF) produced 50.21 wt% bio-oil with deoxygenation degree of 85.49% and 72.82% hydrocarbons content at 500 'C. SA-5.1 promoted the formation of esters in catalytic fast pyrolysis of rattan and the formation of aromatics and hydrocarbons in catalytic fast pyrolysis of karanj shell. AS-EAF promoted the yield of esters and hydrocarbon in bio-oil produced from rattan, and the yield of aromatics in bio-oil produced from karanj shell. The coke deposited on SA-5.1 and AS-EAF in catalytic fast pyrolysis of durian shell is 12.68 wt% and 1.95 wt%, respectively. SA-5.1 has better performance after regeneration in catalytic fast pyrolysis of karanj shell at 500 'C, which the deoyxgenation degree increased from 35.15% to 57.13% and the coke deposition decreased from 15.71 wt% to 11.42 wt%. Although deoxygenation degree of bio-oil produced from karanj shell over AS-EAF reduced after five cycles, the coke deposition was 3.91 wt% after used, which is lower than that of SA-5.1. The kinetic parameters were calculated using Coats-Redfern method. The reaction models of thermal and catalytic pyrolysis of durian shell in Phase II are accounted for one-way diffusion model while the Phase III of thermal and catalytic pyrolysis follows second or third-order reaction models. Catalytic pyrolysis with SA-5.1 exhibited lower activation energy of 115.55 kJ/mol than thermal pyrolysis with activation energy of 170.84 kJ/mol in Phase III, indicates SA-5.1 promoted lignin decomposition.